Psychotropic drugs and Primary Health Care: the subordination of care provision by medicalization in the context of Family Health - Molck, Barbara Vukomanovic [UNESP] (2021)
This study aimed to understand the medicalization of the long-term use of psychotropic drugs from the perception of users of the services provided by a Family Care Center. We conducted a qualitative study using autobiographical narrative analysis using semi-structured interviews with services users selected using purposeful sampling. The thematic analysis revealed that medicalization was incorporated into the life concepts and suffering of service users, which is consistent with social medicalization supported by the biomedical model, which subordinates Primary Health Care work processes.